Response of Growth and Yield of Soybean (Glycine max l. Merril) to the Method and Dose of Leachate Liquid Organic Fertilizer Application - Hasnelly, Hasnelly; Yasin, Syafrimen; Agustian, Agustian; Darmawan, Darmawan (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2021)
The high demand for soybeans cannot yet be met by domestic production. Thus, a way to increase soybean production is necessary, one of which is to use liquid organic fertilizer derived from landfill leachate. This study aimed to examine the application method of liquid organic fertilizer (LOF) from landfill leachate to the soil and leaves and to determine the concentration giving the best growth and yield of soybean plants. The study was a field-research arranged in a completely randomized design (CRD) consisting of six treatments and four replications, which was carried out in a greenhouse. The treatments include A (0 LOF/L water), B (20 ml LOF/L water), C (30 ml LOF/L water, D (40 ml LOF/L water), E (50 ml LOF/L water) and F (60 ml LOF/L water). The liquid organic fertilizer was applied through the soil and leaves at a dose according to the treatments. Â The results showed that the application of liquid organic fertilizer from landfill leachate was better applied to the soil than to the leaves. The liquid organic fertilizer given had a significant effect on the leaf area (cm2), crop weight (g), and plant seed weight (g), but not on the plant height (cm) and stem diameter (cm). Liquid organic fertilizer application is better given to the soil than to the leaves based on the independent T test. The liquid organic fertilizer from landfill leachate at a concentration of 40 ml/L of water had the best effect on the growth and yield of soybean plants.